2020
DOI: 10.1038/s41418-020-0510-7
|View full text |Cite
|
Sign up to set email alerts
|

Drp1 overexpression induces desmin disassembling and drives kinesin-1 activation promoting mitochondrial trafficking in skeletal muscle

Abstract: Mitochondria change distribution across cells following a variety of pathophysiological stimuli. The mechanisms presiding over this redistribution are yet undefined. In a murine model overexpressing Drp1 specifically in skeletal muscle, we find marked mitochondria repositioning in muscle fibres and we demonstrate that Drp1 is involved in this process. Drp1 binds KLC1 and enhances microtubule-dependent transport of mitochondria. Drp1-KLC1 coupling triggers the displacement of KIF5B from kinesin-1 complex increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
0
25
1
Order By: Relevance
“…Regarding the inhibitory effects of Mdivi‐1 on Drp1 in vivo, while we did not directly assess mitochondrial fission and network structure in vivo, we found that Drp1 content in mitochondria fraction and colocalizaion of Drp1 and Cox IV (mitochondria marker) data were reduced in mice treated with Mdivi‐1 for a week, suggesting Mdivi‐1 is effective in inhibiting Drp1 activity. Suprisingly, we did not observe any change in Drp1 Ser616 phosphorylation or Drp1 content in skeletal muscle tissue collected from mice treated with Mdivi‐1, which is in contrast to two studies investigating the effects of Mdivi‐1 injection on skeletal muscle in vivo (Giovarelli et al, 2020; Jheng et al, 2012). It should be noted that Jheng et al, utilized a higher dosage (44 mg/kg BW) and assessed the acute effect of Mdivi‐1 on Drp1 (1‐h post last injection).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the inhibitory effects of Mdivi‐1 on Drp1 in vivo, while we did not directly assess mitochondrial fission and network structure in vivo, we found that Drp1 content in mitochondria fraction and colocalizaion of Drp1 and Cox IV (mitochondria marker) data were reduced in mice treated with Mdivi‐1 for a week, suggesting Mdivi‐1 is effective in inhibiting Drp1 activity. Suprisingly, we did not observe any change in Drp1 Ser616 phosphorylation or Drp1 content in skeletal muscle tissue collected from mice treated with Mdivi‐1, which is in contrast to two studies investigating the effects of Mdivi‐1 injection on skeletal muscle in vivo (Giovarelli et al, 2020; Jheng et al, 2012). It should be noted that Jheng et al, utilized a higher dosage (44 mg/kg BW) and assessed the acute effect of Mdivi‐1 on Drp1 (1‐h post last injection).…”
Section: Discussioncontrasting
confidence: 99%
“…Dynamin‐related protein 1 (Drp1) is a key regulator of mitochondrial fission (Tilokani et al, 2018). While Drp1‐mediated mitochondrial fission is essential in maintaining mitochondrial function and overall skeletal muscle health (Dulac et al, 2020; Favaro et al, 2019), excessive activation/upregulation of Drp1 leads to aberrant mitochondrial fission causing imbalanced mitochondrial dynamics and mitochondrial fragmentation (Giovarelli et al, 2020; Touvier et al, 2015). We and others recently reported that Drp1 is hyperactivated in skeletal muscle from obese insulin‐resistant humans, and this hyperactivation is strongly correlated with impaired skeletal muscle insulin signaling and glucose metabolism (Fealy et al, 2014; Kugler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that promoting a balanced and healthy mitochondrial network by targeting DRP1 could be a useful approach that improves cellular energetics and metabolism in different pathologies [ 83 ]. Studies used the genetic overexpression of DRP1 as a way to increase mitochondrial fission [ 83 , 84 , 85 , 86 ]. Here, we evaluated the effect of pharmacologically mediated DRP1 increase via ATRA.…”
Section: Discussionmentioning
confidence: 99%
“…(b) The sequence of events after depolarization of IMM in PINK1-PARKIN-mediated mitophagy pathway and the ubiquitination of Mfn2, NDP52, NBR1, OPTN. The phagophore engulfment through LC3B interaction [Color figure can be viewed at wileyonlinelibrary.com] testes, lung, skeletal muscle, and hepatocytes (Giovarelli et al, 2020;Ishihara et al, 2009;Kandimalla, Manczak et al, 2016;Touvier et al, 2015). Studies using Drp1 double KO mice revealed that this phenotype is embryonically lethal and thus concluded that Drp1 is essential during development (Wakabayashi et al, 2009).…”
Section: Role Of Drp1 In Mito Chondriamentioning
confidence: 99%
“…Besides, Drp1 is also responsible for peroxisomal fragmentation, SUMOylation, ubiquitination, and glycogen synthase kinase‐3 beta (GSK3β) regulation. Drp1 is usually found in the brain, kidney, liver, spleen, heart, testes, lung, skeletal muscle, and hepatocytes (Giovarelli et al., 2020; Ishihara et al., 2009; Kandimalla, Manczak et al, 2016; Kandimalla & Reddy, 2016; Touvier et al., 2015). Studies using Drp1 double KO mice revealed that this phenotype is embryonically lethal and thus concluded that Drp1 is essential during development (Wakabayashi et al., 2009).…”
Section: Role Of Drp1 In Mitochondriamentioning
confidence: 99%